Electrochemical sensing of Nalbuphine in pharmaceutical samples using amplified MgO/CNTs nanocomposite electrode - Jafari Zare, Samad; Masomi, Mojtaba; Sharifzadeh Baei, Mazyar; Naghizadeh Raeisi, Shahram; Shahidi, Seyed-Ahmad (Journal of Composites and Compounds, 2022)
MgO/CNTs nanocomposite was synthesized by a simple strategy and used for modification of paste electrode. The paraffin oil (PI) and 1-Butyl-3-methylimidazolium methyl sulfate (BMMS) were used as binders for fabrication of MgO/CNTs/PI/BMMS/PE. The results confirm the 9% w:w of MgO/CNTs showed high catalytic activity on nalbuphine signal and this value was used as optimum condition for fabrication of sensor. The MgO/CNTs/PI/BMMS/PE introduce as new analytical sensor for determination of nalbuphine in the concentration range 1.0 nM– 400 µM with detection limit 0.5 nM. In final step, the MgO/CNTs/PI/BMMS/PE was used for monitoring of nalbuphine in injection and serum samples with acceptable recovery data.